2020
DOI: 10.1111/pin.12899
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical and genetic study of BRAFV600E mutation in Japanese patients with ameloblastoma

Abstract: Ameloblastoma is an odontogenic tumor of the jaw. It most frequently occurs in the mandible, and less often in the maxilla. Mandibular ameloblastoma harbors a BRAF mutation that causes a valine (V) to glutamic acid (E) substitution at codon 600 (BRAF V600E ). We examined specimens from 32 Japanese patients to detect the prevalence of the BRAF V600E mutation, and to evaluate the relationship between immunohistochemical (IHC) expression and genetic results, of BRAF V600E+ ameloblastoma. Among the 32 cases, 22 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 23 publications
2
35
1
Order By: Relevance
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the pioneer study by the group of Heikinheimo reported for the first time recurrent activating BRAF p.V600E mutations in ameloblastomas [9]. Considering that MAPK/ERK signaling can be activated by stimulation of transmembrane receptors, including EGFR, and that overexpression of EGFR had previously been reported in ameloblastomas, when [9], [10], [51], [52], [53] e , [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [ V600E mutation in all five ameloblastic carcinoma samples evaluated and this frequency was much higher than reported by previous studies, and therefore we did not add the results to the other ones when calculating mutation frequency.…”
Section: Ameloblastomamentioning
confidence: 99%
“…They further reported the presence of BRAF p.V600E mutation in 67% (23/34) of ameloblastomas by using VE1 immunohistochemistry in cases not suitable for molecular evaluation [52]. Following these pieces of research, several studies have also assessed the presence of BRAF p.V600E in conventional ameloblastoma, either by molecular techniques or a combination of mutation screening and immunohistochemistry, with mutation frequencies varying from 55 to ∼90% [10,[53][54][55][56][57][58][59][60][61][62][63]. In two studies with limited sample numbers, the mutation was detected in all samples [2/2 [64] and 4/4 [65]].…”
Section: Ameloblastomamentioning
confidence: 99%
“…A BRAF mutation, causing valine to glutamic acid substitution at codon 600 (V600E), is present in 40-60% of ameloblastoma cases with mutation-dependent mitogen-activated protein kinase (MAPK) pathway activation [6][7][8][9]. Several studies have described cases of patients with a BRAFV600E mutant that were successfully treated with BRAF inhibitors [10][11][12], suggesting that BRAFV600E signalling might be involved in the development of ameloblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Ensuing studies in a variety of patient populations have further expanded on the frequency and variation of this mutation in ameloblastoma cell lines and tumor specimens. [5][6][7][8][9] Fregnani et al 10 found that BRAF V600E mutation correlates with more aggressive behavior as measured by recurrence, multilocular radiographic appearance, and disruption of basal bone. Investigations by Brown et al 3 and Kelppe et al 7 found the mutation to be associated with earlier age of occurrence, though studies by other groups found no such association.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations by Brown et al 3 and Kelppe et al 7 found the mutation to be associated with earlier age of occurrence, though studies by other groups found no such association. 5,6,8,11 Multiple reports have noted that the BRAF V600E mutation appears almost exclusively in mandibular lesions. 3,4,11 BRAF V600E mutation is well documented in a variety of neoplasms including melanoma, papillary thyroid cancer and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%